2018
DOI: 10.3389/fphar.2017.00982
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Antioxidant and LOX-Mediated Systems Contribute to the Hepatoprotective Activity of Aqueous Partition of Methanol Extract of Muntingia calabura L. Leaves against Paracetamol Intoxication

Abstract: Methanol extract of Muntingia calabura L. (family Muntingiaceae) leaf has been reported to exert various pharmacological activities including hepatoprotection. The present study was carried out to identify the most effective hepatoprotective partition derived from the extract and to determine the mechanisms of action involved. The extract was partitioned using solvents with different polarity to yield petroleum ether (PEMC), ethyl acetate (EAMC), and aqueous (AQMC) extracts. Each extract, at 250 mg/kg, was sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Kersen leaves contain various phytochemicals including saponins, flavonoids, tannins. Flavonoids contained in Kersen leaves have kersen leaf extract administration can reduce levels of ALT / SGPT, AST/SGOT enzymes (Lalihatu & Sudharmono, 2019;Zakaria et al, 2018). Flavonoids as antioxidants have hepatoprotective activity in the concentration range of 1-100 g/mL increasing cell viability and inhibiting cellular leakage of hepatocytes aspartate aminotransferase (AST) and alanine aminotransferase (ALT) (Kočevar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Kersen leaves contain various phytochemicals including saponins, flavonoids, tannins. Flavonoids contained in Kersen leaves have kersen leaf extract administration can reduce levels of ALT / SGPT, AST/SGOT enzymes (Lalihatu & Sudharmono, 2019;Zakaria et al, 2018). Flavonoids as antioxidants have hepatoprotective activity in the concentration range of 1-100 g/mL increasing cell viability and inhibiting cellular leakage of hepatocytes aspartate aminotransferase (AST) and alanine aminotransferase (ALT) (Kočevar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These result showed that KLE was able to reduce levels of serum SGPT in mice. Study conducted by Zakaria et al (2018) showed that KLE administration significantly reduced the level of serum SGOT and SGPT and also increased the activity of endogenous antioxidant enzymes in paracetamolintoxicated rats.…”
Section: The Effect Of the Treatment On Sgot And Sgpt Levelsmentioning
confidence: 99%
“…Administration of the extract reversed the effect of PCM on levels of ALT, AST, and ALP by 85, 82, and 33%, as well as the activity of SOD and CAT by 173 and 68%. The absence of necrosis and haemorrhage was confirmed by microscopic examination and histological scoring of rat liver tissue pretreated with the aqueous partition of methanol extract of M. calabura leaves (250 mg/kg) and followed by the oral exposure of PCM [ 95 ].…”
Section: Medicinal Plantsmentioning
confidence: 99%